Are social conditions important to increase household income? The case of coastal fishers in Makassar City, Indonesia - Rahim, Abd.; Hastuti, Diah Retno Dwi; Bado, Basri; Astuty, Sri (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
Social conditions strongly influence changes in household income because they play a critical role in improving the household welfare of coastal fishing communities. The purpose of the study is to analyze the influence of social conditions on the growth of fisherman's household income in Makassar City, Indonesia. Quantitative research method using survey instrument was addressed to 46 fishers' households by applying the purposive sampling technique. The analytical method used was multiple regression with the exponential function model. This study found that social factors such as the age of the head of the family and the number of working family members contributed to changes in the increase in household income because they had a significant positive effect. On the other hand, the number of dependent household members did not contribute  anything because it had a negative effect on changes in the income level of fishers' households. Likewise, the wife's level of formal education did not affect the household income. Related to social factors as a determinant of improving the fishers' household economy, efforts to increase it can be made through on-fishing and off-fishing. On-fishing is carried out with the support of a gross tonnage boat. Household members do off-fishing in postharvest handling, handling, processing, and marketing marine products.JEL Classification D10; Q22; Z10